BENTUK SAJIAN TARI SRIKANDHI CAKIL - Dwi Maryani (Institut Seni Indonesia Surakarta, 2010)
Srikandhi Cakil dance has the theme of heroism using antawecana (dialogues) and tembang (Javanese songs). Javanese gamelan is used to accompany the dance and at the beginning the accompaniment is ada-ada, Srepeg, ketawang teplek, and then the second srepek, and ada-ada jugag is used before dialogues. In the dialogue, Cakil sits with the knees bent after knowing that he is facing Dewi Woro Srikandhi. To show that Cakil is surprised and gives a respect to Dewi Woro Srikandhi, this scene is accompanied by pathetan jugag. The dialogue is continued to the conversation on the king Jungkung Madiyo’s proposal which is rejected by Srikandhi. The accompaniment of ada-ada jugag is used to make the atmosphere that Cakil is angry. Key words : dance, Srikandi, Cakil